Estudo da interação de amino derivados de quitosana com o plasmídeo VR1412 - Souza, Bruno Corte Alves de [UNESP] (2014)
The current study aimed at the synthesis and characterization of hemocompatible chitosan derivatives and their use in the preparation of nanoparticles for non-viral gene therapy. The project was carried out in two steps, first the synthesis and characterization of the derivatives, followed by studies of the interaction between the chitosan derivatives and the VR1412 plasmid (pDNA), that expresses the β-galactosidase protein. The first step of synthesis was the modification of chitosan by introducing tertiary amino groups, followed by attaching the polyethyleneglycol (PEG) to the chitosan backbone. The study of the interaction between the chitosan derivatives and the pDNA was carried out using the fluorescence, electrophoresis in agarose gel, and light scattering techniques. The study was performed in order to evaluate the effect of structural changes of the chitosan backbone on the strength of interaction and stability of the nanoparticles